An Examination of Domestic Violence Leading to Death: A Case Study from Palembang 2023 - Gracia, Claudia Ave; Pakpahan, Emir Syarif Fatahillah (DiH: Jurnal Ilmu Hukum, 2025)
This study analyzes the Palembang High Court Decision No. 247/PID/2023/PT PLG concerning Domestic Violence (DV) resulting in death. The study aims to evaluate the extent to which the legal application in the verdict aligns with the principles of substantive justice and to assess the legal considerations used by the judges. The methodology employed includes normative juridical and case approaches, with data analyzed from court decisions, legal literature, and other secondary sources. The findings reveal that the judges' legal considerations comply with existing regulations, although challenges remain in integrating gender perspectives and protecting victims' rights. The study recommends enhancing gender understanding within the judicial system and improving psychological rehabilitation for DV victims.